In Vitro and In Vivo Osteogenesis Induced by Icariin and Bone Morphogenetic Protein-2: A Dynamic Observation - Xie, Lina; Liu, Ning; Xiao, Ye; Liu, Yanhui; Yan, Chunge; Wang, Gailing; Jing, Xiangdong (Frontiers in Pharmacology, 2020)
In the present study, we aimed to compare the effects of icariin (ICA) and bone morphogenetic protein-2 (BMP-2) on osteoblast proliferation and osteogenesis in bone defects. We found that in vitro ICA or BMP-2 treatment is able to increase osteoblast proliferation, which was detected by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT). Specifically, ICA at a concentration of 30 µg/ml had the strongest ability to promote cell proliferation, which is equivalent with the effect of BMP-2 at a concentration of 50 µg/ml. Furthermore, Western blot and RT-qPCR analyses showed that treatment with ICA (20–30 µg/ml) had similar increase effect with BMP-2 (50 µg/ml) on the protein and mRNA levels of BMP-2, osteoprotegerin (OPG), and alkaline phosphatase (ALP) mRNAs. In addition, the animal model of bone defects was successfully prepared. The in vivo data showed that compared with the control group, highest osteogenesis in the ICA or BMP-2 groups was observed at different observational times. Four weeks after surgery, osteogenesis in the BMP-2 group was slightly higher than that in the ICA group, but there was no significant difference between the two groups until the eighth week. ICA promotes osteoblast proliferation by stimulating the expression of BMP-2 and OPG proteins and upregulating the expression of BMP-2, OPG, and ALP mRNAs. ICA at a certain concentration has the same osteogenic effect as BMP-2. ICA or BMP-2 composite nanomaterials can be used as a framework to guide bone regeneration and promote osteogenesis. In addition, the combined use of hematoxylin-eosin and Goldner’s trichrome staining techniques contributes to acquiring better bone morphometric information about bone defects.